2017
DOI: 10.1016/j.enfcli.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Empatía, soledad, desgaste y satisfacción personal en Enfermeras de cuidados paliativos y atención domiciliaria de Chile

Abstract: These findings confirm the important role that empathy plays in the prevention of loneliness and burnout, and in the promotion of life satisfaction. Evidence found suggests that empathetic abilities can be improved by the professional experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 35 publications
4
16
0
8
Order By: Relevance
“…(Table 3). background, duration of work [16][17][18][19]23 , mode of work 16 , status of being satisfied with the professional life and taking education after graduation 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 3). background, duration of work [16][17][18][19]23 , mode of work 16 , status of being satisfied with the professional life and taking education after graduation 17…”
Section: Resultsmentioning
confidence: 99%
“…do not affect their empathic tendencies, which corroborate our findings. On the other hand, in the study by Akgün ġahin et al15 it was found that the communication and empathy skills of the nurses vary depending on their age and educational background, and in the study by Marilaf Caro et al23 and Alkan18 , it was found that the empathic tendency level of the nurses increase as their professional experience increases. While the factors affecting the empathic tendency levels and communication skills of the nurses vary depending on the studies, it is thought that the education, work conditions and personal characteristics of nurses can affect this situation.In our study, it was found that receiving education on empathy and developingcommunication skills after graduation does not affect the empathic tendency levels and communication skills of the nurses.…”
mentioning
confidence: 96%
“…One possible explanation is that the expressive arts intervention provided an accessible community of likeminded professionals who were seeking to cope with similar stresses. In this effort, their social support was increased, which in turn decreased isolation, a symptom that highly correlates with burnout (Karaoglu et al, 2015). Another possible hypothesis is that the expressive arts intervention brought the participants awareness to their emotions and then the psycho-education provided the skills necessary to improve coping.…”
Section: Discussionmentioning
confidence: 99%
“…Há também pesquisas investigando a relação de empatia com solidão, sendo esta última compreendida como um aspecto estável e duradouro de distanciamento social e sofrimento devido ao isolamento (Barroso, Andrade, Midgett, & Carvalho, 2016). Os resultados mostram correlações inversas entre os construtos, com índices variando entre r = -0,41 e -0,42 (Beadle, Keady, Brown, Tranel, & Paradiso, 2012;Marilaf Caro, San-Martín, Delgado--Bolton, & Vivanco, 2017).…”
Section: Estudios De Validez Del Cuestionario Online De Empatía Resumenunclassified